Thoracoscopic surgery for hepatocellular carcinoma located in the hepatic dome: Technical aspect and oncological results. Issue 3 (12th September 2019) - Yamao, Takanobu; Imai, Katsunori; Yamashita, Yo‐ichi; Umezaki, Naoki; Tsukamoto, Masayo; Kitano, Yuki; Arima, Kota; Miyata, Tatsunori; Nakagawa, Shigeki; Okabe, Hirohisa; Nitta, Hidetoshi; Chikamoto, Akira; et al.
Abstract: Introduction: The objective of this study was to describe the surgical techniques for a thoracoscopic approach to treat hepatocellular carcinoma in the hepatic dome. Also, safety, feasibility, and long‐term outcomes were evaluated. Methods: Surgical procedures were selected based on liver function, the extent and location of the tumor, and each patient's general condition. Thoracoscopic hepatic resection was performed under direct vision through a diaphragmatic incision. Thoracoscopic radiofrequency ablation (TRFA) was performed either with a transdiaphragmatic puncture for deeply located tumors or under direct vision through a diaphragmatic incision for subcapsular tumors. Results: Thoracoscopic surgery was indicated for 107 patients with hepatocellular carcinoma in the hepatic dome. Among these patients, 5 underwent hepatectomy and 102 underwent radiofrequency ablation, which was more frequently employed in patients with impaired liver function. Of the patients who underwent radiofrequency ablation, 43 (42.2%) required a diaphragmatic incision. In the thoracoscopic hepatic resection group and TRFA group, the median operating time was 350 and 197 minutes, the median blood loss was 200 and 5 mL, and the complication rate was 12.7% and 20.0%, respectively. The 5‐year overall and disease‐free survival rates were 100% and 50.0% in the thoracoscopic hepatic resection group, respectively, and 60.7% and 18.1% in the TRFA group, respectively. Local recurrence after TRFA was observed in 10 patients (9.8%). Conclusion: The thoracoscopic approach is safe and feasible, with promising short‐ and long‐term outcomes. It could serve as a treatment option for hepatocellular carcinoma in the hepatic dome.